Parametric Study on The Bearing Capacity of Down-hole Dynamic Compaction - Nulya M, Anisya Aura; Solin, Dian Purnamawati; Farichah, Himatul (Universitas Negeri Yogyakarta, 2023)
The DDC method is well known as Down-Hole Dynamic Compaction, an effective ground treatment method. DDC combines dynamic compaction and soil replacement methods to enhance bearing capacity, reduce settlement, minimize the potential for collapse, and mitigate liquefaction. DDC has been commonly used to stabilize collapsible soil, DDC basically forms a column inside the soil stratum which is similar to a stone column except DDC materials are put in sequence and then compacted by using DDC hammer, this is known as the self-tamping method. DDC is considered as a suitable method for soft soil improvement. This study modeled DDC as reinforcement for runway area which is predominantly soft soil in the study location. DDC is modeled with various dimension and spacing to assess its impact on bearing capacity and settlement, thereby simplifying the selection of suitable dimension during installation. The results show that the stress induced by external loads on Down-hole Dynamic Compaction (DDC) rises in correlation with the spacing between DDC installations. The peak stress was documented on a DDC unit with a 1-meter diameter positioned at a distance of 2.5 meters from the other DDC units, measuring 83.9 kN/m2. The highest stress level was recorded in the soil surrounding a DDC unit with a 1.5-meter diameter, which was positioned 3 meters away from other DDC units, measuring 157.89 kN/m2. The highest bearing capacity was achieved when a DDC with a diameter of 1.5 meters was positioned at a distance of 3 meters, resulting in a bearing capacity value of 1407.32 kN/m2.